Community Service Eco-Pounding Brajan Village, Brajan District, Mojosongo District, Boyolali District - Rahmana, Viola; Wanda Julisna; Dimar Prabawati; Soelistijono, R; Daryanti; Sari, Siti Mardhika; Aziez, Achmad Fatchul (Journal of Community Capacity Empowerment, 2024)
Eco Pounding is a fabric dyeing technique that uses natural materials such as leaves, flowers, or branches to create fabric motifs. This technique is done by pounding natural materials onto the fabric using a hammer, so that the colours or motifs produced on the fabric match the original texture or shape of the natural materials used. Eco pounding is an eco-print technique that uses natural materials to create motifs on fabric, and this technique is very easy to do and uses materials that can be found around. Shibori Arashi dyeing technique is a fabric dyeing technique that utilises bonding and dyeing to determine the motif on the fabric. In this technique, the fabric is patterned using a pattern that has been made then crimped according to the pattern, then tied firmly using rope or rubber. After that, the fabric is dyed in a dye made from indigo leaves. Shibori Arashi dyeing usually produces striped motifs.